2004
DOI: 10.3928/0191-3913-20040101-08
|View full text |Cite
|
Sign up to set email alerts
|

Screening for Retinopathy of Prematurity: Results of a Retrospective 3-Year Study of 502 Infants

Abstract: Purpose: To describe the surveillance, results of screening, and treatment of retinopathy of prematurity (ROP) in a university hospital setting in southeast France. Patients and Methods: Five hundred two premature infants were included in the screening protocol between January 1997 and December 1999. Criteria for inclusion in the study were a gestational age of 32 weeks or younger, a birth weight of less than 1,501 g, or both. The first fundus examination was performed between 4 and 6 weeks of life. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…[7121516] In a study conducted in our center in 1996-97, ROP was found among 64.5% of babies with birth weight of less than 2000 g.[17] The higher incidence of ROP could be due to smaller babies in the earlier cohort. [17] A decreasing incidence of ROP has been observed by some authors[4519] and this has been attributed to the introduction of use of Surfactant[5] or to the improving neonatal care and better monitoring of oxygen saturation. [19]…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[7121516] In a study conducted in our center in 1996-97, ROP was found among 64.5% of babies with birth weight of less than 2000 g.[17] The higher incidence of ROP could be due to smaller babies in the earlier cohort. [17] A decreasing incidence of ROP has been observed by some authors[4519] and this has been attributed to the introduction of use of Surfactant[5] or to the improving neonatal care and better monitoring of oxygen saturation. [19]…”
Section: Discussionmentioning
confidence: 99%
“…[815] Some studies have reported incidence of less than 5% of severe ROP needing laser treatment. [4–6] Chow et al [21] reported zero incidence of severe ROP needing treatment and attributed it to a protocol of improved management of oxygen administration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The prevalence of RoP in a previous study was 68% in stage I, 23.5% in stage II, and 8.5% in stage III. 23 Also, another study reported that 30.2% of infants under 1500 g suffered from stage I and II RoP and 16.6% of them suffered from stage III and above. In infants weighing 1500 to 2500 g, 3.2% had stage I and II RoP, and 0.6% had stage III and above.…”
Section: Discussionmentioning
confidence: 96%